2021
DOI: 10.3390/su13041945
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Water-Related Pollution on Food Systems in Transition: The Case of Northern Vietnam

Abstract: In Vietnam, agricultural practices such as fertilizer and pesticide use affect the landscape as well as the availability and safety of food. For instance, pesticides and fertilizer end up in surface water used for drinking water, crop irrigation, and in fish tanks. However, the link to actual food consumption and health is complex and information is lacking. This study considers potential water-related exposure to toxic hazards in northern Vietnam food systems, through the consumption of food commodities and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…In general, the results of previous studies have mainly indicated an increased concentration of heavy metals and arsenic in honey produced near mining areas; however, in most cases, they did not exceed illegal limits [12], and hence, honey is safe for use and human health [66,67]. However, some authors have called for caution [18,63,68,69], which is also the case with the authors of this study.…”
Section: Discussionsupporting
confidence: 55%
“…In general, the results of previous studies have mainly indicated an increased concentration of heavy metals and arsenic in honey produced near mining areas; however, in most cases, they did not exceed illegal limits [12], and hence, honey is safe for use and human health [66,67]. However, some authors have called for caution [18,63,68,69], which is also the case with the authors of this study.…”
Section: Discussionsupporting
confidence: 55%
“…Water contamination can harm agricultural fields, causing crops and cattle to absorb pollutants. Contaminated food and water can lead to the absorption of toxic substances, which can affect energy balance and metabolic processes in the body (Linderhof et al, 2021). The risk of contaminated food and water is increased in areas where river water is used for agriculture or drinking water supplies.…”
Section: Contamination Of Food and Watermentioning
confidence: 99%
“…In spite of the fact that water is an abundant resource on earth, pollution and waste lead to a substantial reduction in the amount of water available for human consumption, causing a water shortage in some regions [ 19 ]. A variety of sources contribute to water pollution, including chemical disposal of pharmaceuticals, industrial processes, agriculture, and household waste [ 20 ]. In light of the importance of water and the increasing pollution in rivers, oceans, and lakes, the promotion and assessment of water quality have become key priorities in environmental policy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In light of the importance of water and the increasing pollution in rivers, oceans, and lakes, the promotion and assessment of water quality have become key priorities in environmental policy [ 19 ]. Moreover, water pollution also impacts aquatic species, which are exposed to environmental pollution, resulting in an increase in mortality [ 20 ]. In addition to polluting aquatic species, the toxins in fish and other aquatic species can also be transmitted to other aquatic and non-aquatic species, including humans, via the food chain [ 21 ].…”
Section: Introductionmentioning
confidence: 99%